Development of a Pelvic Discomfort Index to Evaluate Outcome following Fixation for Pelvic Ring Injury - Tomas Borg; Bjorn Hernefalk; Marianne Carlsson; Sune Larsson (Journal of Orthopaedic Surgery, 2015)
Purpose. To develop a pelvic discomfort index (PDI) to evaluate outcome following fixation for pelvic ring injury. Methods. 29 female and 44 male consecutive patients (mean age, 36 years) underwent internal fixation for pelvic ring injury of type B1 (n=10), B2 (n=22), B3 (n=15), C1 (n=18), C2 (n=5), and C3 (n=3), based on the AO/OTA classification. At postoperative 6, 12, and 24 months, patients were asked to assess their discomfort in the pelvis using a 14-item questionnaire. Three questions were open-ended, and responses were categorised by a single assessor. The remaining 11 questions were closed-ended and had 6 ordinal options from ‘no discomfort’ (score=0) to ‘extremely severe discomfort’ (score=5). The content validity and relevance of the 11 closed-ended questions was determined. The 14-item questionnaire was compared with the 36-item Short Form Health Survey (SF-36). Results. Respectively at postoperative 6, 12, and 24 months, 78%, 71%, and 71% of the patients completed the 14-item questionnaire. Based on the factor analysis and responses to the open-ended questions, the number of items was reduced to 6 including pain, walking, mobility of the hips, loss of sensation in the legs, sexual life, and operation scar. Four factors could explain 96% of the total variance. The first factor involved the first 3 items (pain, walking, and hip motion) and addressed ‘pelvis’, whereas 3 factors involved the remaining items and each addressed peripheral neurology, sexual life, and operation scar. A PDI was developed using these 6 items. The PDI had high internal reliability (α=0.89), adequate content and criterion validity, and moderate correlation with the SF-36 total score or scores of physical function, bodily pain, and general health ( r =0.50–0.77). Conclusion. The PDI provides valid, specific, and relevant information to assess outcome following fixation for pelvic ring injury.